2011
DOI: 10.1007/s12032-011-0127-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of EphA2 correlates with epithelial–mesenchymal transition-related proteins in gastric cancer and their prognostic importance for postoperative patients

Abstract: The expression of EphA2 and three epithelial-mesenchymal transition-related proteins (E-cadherin, β-catenin and vimentin) was detected by immunohistochemistry in human gastric cancer and normal gastric mucosa. The expression of EphA2 and vimentin was significantly higher in gastric cancer tissues than in normal gastric mucosa tissues, and similar results were found for negative E-cadherin expression and ectopic β-catenin expression. Further analysis showed that the expression of EphA2 was closely correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…EPHA2 is overexpressed in a wide range of cancers and is associated with poor prognosis [25]. Many recent studies investigated the RTKs such as EphA2 and reported them as targets for molecular therapy for GAC [26][27][28][29], and also proved that EphA2 overexpression was positively correlated with factors that controlled angiogenesis and invasion in cancer cells because EphA2 receptor activation allowed vascular endothelial growth factor (VEGF)-dependent endothelial cell transport, sprouting, survival and expression of metalloproteinase, and these may be the causes of the poor clinical outcome of cancer patients with EphA2 overexpression, moreover the EphA2-EphrinA1 signaling axis regulates many steps that are essential for carcinogenesis and stimulation of downstream molecules like the phosphatidyl inositol 3' kinases (PI3K), mitogen activated protein kinases (MAPK) and integrins along with epidermal growth factor receptor(EGFR) that regulate cell adhesion, cancer cell growth, metastases and development of vascular network.…”
Section: Discussionmentioning
confidence: 99%
“…EPHA2 is overexpressed in a wide range of cancers and is associated with poor prognosis [25]. Many recent studies investigated the RTKs such as EphA2 and reported them as targets for molecular therapy for GAC [26][27][28][29], and also proved that EphA2 overexpression was positively correlated with factors that controlled angiogenesis and invasion in cancer cells because EphA2 receptor activation allowed vascular endothelial growth factor (VEGF)-dependent endothelial cell transport, sprouting, survival and expression of metalloproteinase, and these may be the causes of the poor clinical outcome of cancer patients with EphA2 overexpression, moreover the EphA2-EphrinA1 signaling axis regulates many steps that are essential for carcinogenesis and stimulation of downstream molecules like the phosphatidyl inositol 3' kinases (PI3K), mitogen activated protein kinases (MAPK) and integrins along with epidermal growth factor receptor(EGFR) that regulate cell adhesion, cancer cell growth, metastases and development of vascular network.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a previous study in lung carcinoma (15), the present results support EphA2 expression as an important index of disease progression. As EphA2 can be highly expressed in a broad range of cancer types (2022), the prognostic utility of this marker may prove significant in the monitoring and clinical management of a large cohort of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, TGF-β activates other EMT-related signaling pathways, such as Notch, Wnt/β-catenin, and integrin[10]. Recently, a number of studies including ours have suggested that EPH receptors play a role in the EMT process[26][28]. However, the mechanism by which EPH receptors regulate EMT is still largely unknown.…”
Section: Emtmentioning
confidence: 95%
“…Recently, EPH receptors have been found to play an important role in many aspects of EMT[26][28], including induction of a mesenchymal-like phenotype (e.g., an E-cadherin–negative and vimentin-positive phenotype) and inhibition of epithelial characteristics (e.g., an E-caherin-positive and vimentin-negative phenotype)[46]. Moreover, EPH receptors crosstalk with EMT-related signal transduction pathways such as those induced by NF-κB and PI3K[54],[55].…”
Section: The Role Of Eph Receptors In Emtmentioning
confidence: 99%
See 1 more Smart Citation